Comparison of tissue adhesive (N-butyl-2-cyanoacrylate) versus conventional suturing in umbilical hernia surgeries - Dua, Atul; A., Nawaz Shariff; Prasad, K. Krishna (International Surgery Journal, 2021)
Background: Umbilical hernia is a common problem encountered mostly in women. Conventional suturing is used as a traditional method for closure of skin in umbilical hernia surgeries. N-butyl-2-cyanoacrylate glue can be used as an alternative where tissue loss is minimal, minimal scarring, no significant bacterial infection and less postoperative pain. The aim of this study was to determine the effectiveness of tissue adhesive in the closure of umbilical skin incisions compared to conventional sutures. Methods: A prospective study was conducted including 30 patients with umbilical hernia. Patients were allocated into two groups using odd and even method: group A and B. Patients of group A underwent skin closure with topical tissue adhesive and that of group B underwent skin closure with conventional sutures. Skin closure time, postoperative pain, scar assessment using Vancouver scar scale and surgical site infection were recorded. IBS-statistical package for the social sciences (SPSS) 22 version was used to analyse the data. Results: 57% females and 43% males were included in the study. The age of the patients ranged between 18 and 60 years in both the groups. All patients had chief complaint of swelling in the umbilical area. Group A (tissue adhesive) patients had lesser skin closure time and cosmetically better scar than group B (conventional suturing) patients. Surgical site infection was seen in 2 patients in group B and 1 patient in group A. Conclusions: Tissue adhesive is superior as compared to conventional suture in terms of skin closure time, cosmesis, postoperative pain and postoperative surgical complications.